Early development of vaginal shortening during radiation therapy for endometrial or cervical cancer. Issue 3 (1st May 2001) - Katz, A.; Njuguna, E.; Rakowsky, E.; Sulkes, A.; Sulkes, J.; Fenig, E.
Abstract : Vaginal necrosis can occur following radiation therapy for gynecological malignancies. The distal vaginal mucosa has a poorer radiation tolerance than the mucosa in the upper region. We examined the extent of vaginal shortening in patients treated by intravaginal brachytherapy with or without pelvic irradiation. Maximal extension of the vaginal cylinder above the pubis was measured for each insertion. We found that the difference in mean values between insertions (2.3 vs. 1.7 cm) was highly statistically significant ( P < 0.0001). Our study shows that vaginal shortening can occur during the course of intracavity and external irradiation. These alterations in vaginal anatomy can have important consequences on doses received by the distal vaginal mucosa.